Air quality impacts of fuel cell electric hydrogen vehicles with high levels of renewable power generation. (15th October 2016) - Mac Kinnon, Michael; Shaffer, Brendan; Carreras-Sospedra, Marc; Dabdub, Donald; Samuelsen, G.S.; Brouwer, Jacob
Abstract: The introduction of fuel cell electric vehicles (FCEV) operating on hydrogen is a key strategy to mitigate pollutant emissions from the light duty vehicle (LDV) transportation sector in pursuit of air quality (AQ) improvements. Further, concomitant increases in renewable power generation could assist in achieving benefits via electrolysis-provided hydrogen as a vehicle fuel. However, it is unclear (1) reductions in emissions translate to changes in primary and secondary pollutant concentrations and (2) how effects compare to those from emissions in other transport sectors including heavy duty vehicles (HDV). This work assesses how the adoption of FCEVs in counties expected to support alternative LDV technologies affect atmospheric concentrations of ozone and fine particulate matter (PM2.5 ) throughout California (CA) in the year 2055 relative to a gasoline vehicle baseline. Further, impacts of reducing HDV emissions are explored to facilitate comparison among technology classes. A base year emissions inventory is grown to 2055 representing a business-as-usual progression of economic sectors, including primarily petroleum fuel consumption by LDV and HDVs. Emissions are spatially and temporally resolved and used in simulations of atmospheric chemistry and transport to evaluate distributions of primary and secondary pollutants respective to baseline. Results indicate that light-duty FCEV Cases achieve significant reductions in ozone and PM2.5 when LDV market shares reach 50–100% in early adoption counties, including areas distant from deployment sites. Reflecting a cleaner LDV baseline fleet in 2055, emissions from HDVs impact ozone and PM2.5 at comparable or greater levels than light duty FCEVs. Additionally, the importance of emissions from petroleum fuel infrastructure (PFI) activity is demonstrated in impacts on ozone and PM2.5 burdens, with large refinery complexes representing a key source of air pollution in 2055. Results presented provide insight into light duty FCEV deployment strategies that can achieve maximum reductions in ozone and PM2.5 and will assist decision makers in developing effective transportation sector AQ mitigation strategies. Highlights: Impacts on ozone and PM2.5 in 2055 are assessed from FCEV deployment in CA. Notable improvements occur when FCEV reach high levels (i.e., >50% of light duty vehicles). FCEV in the heavy duty vehicle sector can achieve comparable or enhanced AQ benefits. The production and distribution of petroleum fuels are key driver of AQ impacts in 2055.